A comprehensive review of banana based paper - Nor Azman, Nor Farah Amirah; Othman, Siti Amira
This paper reviews the process, product and future applications of banana-based paper. The utilization of bark tree to produce paper has been practiced for centuries. Unfortunately, deforestation can cause climate change, desertification, soil erosion, fewer crops, flooding, increased greenhouse gases in the atmosphere and a host of many environmental problems. As alternatives, many raw materials based on plant were produced for paper and banana stem is one of them. Banana stem is easily collected from banana trees after collection of banana fruits. It is the flower stalk of the banana plant. The rough and hard outer layers are removed to reveal the stark white. Once they are removed and dried, they are boiled, shredded and rinsed to create pulp. The pulp was put into mold and pressed into sheets of paper. This product gave a huge promising as viable product especially in commercialization, cost structure, paper superior properties and positive environmental benefits. Nowadays, the market of paper is overwhelming because it can be used to make a variety of products that helps world economy and have wide scope to create new market.